2012
DOI: 10.1007/s10899-012-9340-y
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Responsible Gambling: The Relative Effectiveness of Education-Based Animation and Monetary Limit Setting Pop-up Messages Among Electronic Gaming Machine Players

Abstract: Although most gamblers set a monetary limit on their play, many exceed this limit—an antecedent of problematic gambling. Responsible gambling tools may assist players to gamble within their means. Historically, however, the impact of such tools has been assessed in isolation. In the current research, two responsible gambling tools that target adherence to a monetary limit were assessed among 72 electronic gaming machine (EGM) players. Participants watched an educational animation explaining how EGMs work (or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 32 publications
2
62
1
Order By: Relevance
“…The reported impact of messages being read, or causing respondents to look at other players or machines, talk to other players, or take actions other than continued play suggests that they created at least a small break in play. Breaks in play, even short periods, are important to enable gamblers to be aware of the amount of time and money they have spent, check in with their surroundings and be able to more accurately assess their current situation and make an informed decision regarding their ongoing gambling (Monaghan & Blaszczynski, 2010b;Wohl, Gainsbury, Stewart, & Sztainert, 2013). Immediate behavioural changes as a result of seeing the messages were not readily apparent.…”
Section: Discussionmentioning
confidence: 99%
“…The reported impact of messages being read, or causing respondents to look at other players or machines, talk to other players, or take actions other than continued play suggests that they created at least a small break in play. Breaks in play, even short periods, are important to enable gamblers to be aware of the amount of time and money they have spent, check in with their surroundings and be able to more accurately assess their current situation and make an informed decision regarding their ongoing gambling (Monaghan & Blaszczynski, 2010b;Wohl, Gainsbury, Stewart, & Sztainert, 2013). Immediate behavioural changes as a result of seeing the messages were not readily apparent.…”
Section: Discussionmentioning
confidence: 99%
“…Players should be introduced to responsible gaming from the very start of their gambling during registration on a specific site. Wohl et al (2013) showed that players who watched an educational animation more often stayed within their preset limits compared to players who did not watch the video.…”
Section: Empirical Studies On Limit Setting In Gamblingmentioning
confidence: 99%
“…Evidence supporting variations of pop-up messages as effective harm-minimization tools has developed since the design of the New Zealand intervention (e.g., Blaszczynski et al, 2014;Monaghan, 2008;Monaghan & Blaszczynski, 2010;Wohl et al, 2013), but regardless of their sophistication, these messages indicate a gambler who has been gambling for an extended time, and those who report typically seeing three or more pop-up messages in a gambling session are more likely to be problem gamblers . The pop-up messages provide an opportunity for vigilant venue staff to interact with patrons, and it would seem logical to suggest that pop-up messages would be more effective if supplemented consistently with staff intervention (e.g., Delfabbro et al, 2007;Department of Internal Affairs, 2013;Griffiths, 2009;Productivity Commission, 2010;Tse et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…After 15 s, the gambler is given the option of continuing to gamble or cashing out. Although empirical evidence on the effectiveness of pop-up messages and the sophistication of the messages themselves has developed since their introduction (e.g., Blaszczynski, Gainsbury, & Karlov, 2014;Monaghan, 2008;Monaghan & Blaszczynski, 2010;Wohl, Gainsbury, Stewart, & Sztainert, 2013), the early uptake of this system in New Zealand means the intervention itself was informed by just two studies (Ladouceur & Sévigny, 2003;Shellink & Shrans, 2002). The frequency of occurrence of pop-up messages lent confidence that all occurrences regarding observed gamblers could be documented.…”
Section: Introductionmentioning
confidence: 99%